Personnel policies : guides for bank management - Mccurry, Charles M.; Bank Administration Institute (Bank Administration Institute : Park Ridge, Illinois, 1974)
This book provides the foundation for many personnel practices and procedures. They are a product of management's beliefs and goals, and express the underlying principles and guidelines by which decisions are mad and actions are taken in matters involving employees.
Includes bibliographical references and index.
hza 24/07/2018
Loans
Keywords: personnel policy; United States